Efektivitas Pemanfaatan Hasil Tes Stifin terhadap Hasil Belajar PAI Siswa SD IT Madani 2 Payakumbuh - Gusti Mulia Sari; Siska Yulia Rahmi (YASIN, 2026)
Differences in students’ characteristics and learning tendencies in Islamic Religious Education (PAI) learning need to be understood by teachers so that the learning process can take place more optimally. One effort that can be made is to map students’ characteristics through the STIFIn test. This study aimed to describe students’ STIFIn test results, PAI learning outcomes, and the profile of PAI learning outcomes based on the STIFIn test mapping of fifth-grade students at SD IT Madani 2 Payakumbuh. This study used a descriptive quantitative approach with fifth-grade students of SD IT Madani 2 Payakumbuh as the subjects. Data were collected through questionnaires, documentation of PAI scores, and interviews, and then analyzed by presenting the data in the form of tables and percentages and describing them in accordance with the research objectives. The results showed that the STIFIn test mapping of fifth-grade students revealed diverse intelligence machines, including Sensing, Thinking, Intuiting, Feeling, and Instinct. In general, students’ PAI learning outcomes had achieved learning mastery in accordance with the Minimum Mastery Criteria (KKM) established by the school, although a small number of students had not yet achieved mastery. The STIFIn test result mapping provided an overview of students’ characteristics and learning tendencies that can be used as supporting information for teachers in understanding students’ learning needs in PAI learning. The conclusion of this study emphasizes that mapping students’ characteristics through the STIFIn test contributes to supporting more adaptive PAI learning oriented toward the diversity of students’ learning potential.